Age-associated interplay between zinc deficiency and Golgi stress hinders microtubule-dependent cellular signaling and epigenetic control - Brito, Sofia; Heo, Hyojin; Kim, Jinyoung; Cha, Byungsun; Jeong, Youngdo; Choi, Wooseon; Shrestha, Chandani; Lee, Gang Hyoung; Park, Sun Ju; Yoon, Ki Bok; Oh-Hashi, Kentaro; Kim, Sung Tae; et al. (Developmental Cell, 2025)
Golgi abnormalities have been linked to aging and age-related diseases, yet the underlying causes and functional consequences remain poorly understood. This study identifies the interaction between age-associated zinc deficiency and Golgi stress as a critical factor in cellular aging. Senescent Golgi bodies from human fibroblasts show a fragmented Golgi structure, associated with a decreased interaction of the zinc-dependent Golgi-stacking protein complex Golgin45-GRASP55. Golgi stress is increased, and functions such as glycosylation and vesicle transport are impaired. These disturbances promote Golgi and perinuclear microtubule disassembly and subsequent mislocalization of intracellular proteins associated with cellular signaling and epigenetic control. Pharmacological induction of Golgi stress or zinc deficiency, or ablation of the Golgi-associated zinc transporter gene Zip13 in mouse fibroblasts, replicate the characteristics of cellular senescence, emphasizing the critical role of Golgi-zinc homeostasis. These findings highlight the importance of adequate zinc intake and suggest targeting Golgi dysfunction as a therapeutic strategy for alleviating age-related cellular decline.
Keywords: Aging; Animals; Cation Transport Proteins; Cellular Senescence; Epigenesis, Genetic; Fibroblasts; Golgi Apparatus; Humans; Mice; Microtubules; Signal Transduction; Zinc; aging; epigenetics; Golgi; GRASP55; microtubules; senescence; signaling; zinc; zinc transporter; ZIP13